Albrecht dürer's Material World. - Wouk, Edward H. (Manchester University Press, 2023)
This highly illustrated catalogue presents new essays on Albrecht Dürer, focusing on an understudied aspect of his practice: the material worlds of manufacture, design and trade.
Description based upon print version of record.
Keywords: Dürer, Albrecht, -- 1471-1528 -- Exhibitions.; Material culture in art -- Exhibitions.; Culture matérielle dans l'art -- Expositions.